Flying Steamer-Duck (Tachyeres Patachonicus) egg found in a Kelp Gull (Larus dominicanus) nest in Northwestern Patagonia - Motta, Luciana Maria (2015)
While conducting fieldwork in Kelp Gull (Larus dominicanus) colonies of Lake Nahuel Huapi islets, we found a Flying Steamer-Duck (Tachyeres patachonicus) egg in a Kelp Gull nest. A camera trap was installed in an attempt to record egg developement, but technical problems prevented us from observing the steamer-duck´s egg hatching. Nevertheless, pictures and videos obtained allowed us to confirm that the nest belonged to a Kelp Gull pair, and that both gulls eggs were successful, as we observed the chicks in our following visits to the colony. The Flying Steamer-Duck egg dissapeared by the next time we checked the nest. When an alien egg is found in the nest of another species, brood parasitism is probably the most plausible explanation. Alternatively, the presence of the alien egg in the nest may be due to gull behavior. It is known that gulls are important predators of eggs and young of many species of ducks, and there are reports of California Gulls (Larus californicus) carrying eggs of other species to their nests with feeding purposes but once in the nest, the nesting impulse overpowers the feeding impulse, and the eggs are finally incubated. Our observation does not allow us to determine the final factors responsible for the presence of the Flying Steamer-Duck egg in the Kelp Gull?s nest, and alternative explanations are possible. In any case, our observation constitutes the first record of a Flying Steamer-Duck egg found in the nest of another species.